3D Talar Kinematics During External Rotation Stress Testing in Hindfoot Varus and Valgus Using a Model of Syndesmotic and Deep Deltoid Instability. (July 2019) - Goetz, Jessica E.; Vaseenon, Tanawat; Tochigi, Yuki; Amendola, Annunziato; Femino, John E.
Background: External rotation stress (ERS) identifies ankle instability after fibular reduction of rotational ankle injuries. Combined hindfoot and ankle motions and an inconsistent starting position could mask differing degrees of instability resulting from syndesmotic and/or deltoid ligament disruption. The goal of this work was to use full 3D talar kinematics to evaluate the effects of hindfoot orientation and foot starting position during ERS on the ability to detect instability caused by ligament disruptions. Methods: Six cadaveric ankles with metallic fiducial markers were CT scanned in neutral and 3 stress positions: varus hindfoot internal rotation stress (IRS-var), valgus hindfoot ERS (ERS-val), and varus hindfoot ERS (ERS-var). Scans were obtained in stress positions after transecting the deep deltoid ligament (tDDL) and then the syndesmotic ligaments (tDDL+Syn). Talar rotations and translations were computed in the axial, coronal, and sagittal planes in each stress position. Changes in a fixed center of rotation (CoR) relative to the intact sequence were calculated. Results: Axial plane rotation beginning from IRS-var increased significantly for each level of ligamentous instability ( P < .05 for all conditions) (10.9 degrees, intact; 14.1 degrees, tDDL; 22.7 degrees, tDDL+Syn during ERS-val; and 16.4 degrees, intact; 23.1 degrees, tDDL; 29.9 degrees, tDDL+Syn during ERS-var). With ERS-val, the talar CoR moved medially (3.6-5.4 mm) and posteriorly (0.5-5.2 mm); ERS-var moved anterior/laterally or posterior/medially depending on the specific ligamentous instability. With tDDL+Syn the ankle became grossly unstable and there were no clear trends in sagittal/coronal rotation or translation. Conclusion: An ERS test from internal to external rotation consistently differentiates between normal, tDDL, and tDDL+Syn. Talar CoR moved outside the mortise with ligamentous instability. Clinical Relevance: Significant residual deep deltoid instability is likely underrecognized with current practice. The most discriminatory test for detecting such instability in our laboratory was an ERS test performed by internally rotating the foot to a hard, bony endpoint, positioning the hindfoot in varus, and then performing the entire external rotation maneuver while maintaining the varus hindfoot position.